2015
DOI: 10.1016/s0140-6736(14)60931-4
|View full text |Cite
|
Sign up to set email alerts
|

Global epidemiology of HIV among female sex workers: influence of structural determinants

Abstract: SUMMARY Female sex workers (FSWs) bear a disproportionately large burden of HIV infection worldwide. Despite decades of research and programme activity, the epidemiology of HIV and the role that structural determinants have in mitigating or potentiating HIV epidemics and access to care for FSWs is poorly understood. We reviewed available published data for HIV prevalence and incidence, condom use, and structural determinants among this group. Only 87 (43%) of 204 unique studies reviewed explicitly examined str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
803
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 759 publications
(844 citation statements)
references
References 124 publications
(294 reference statements)
25
803
0
16
Order By: Relevance
“…The structural components of this profile, rooted in gender and class inequalities, reflect fundamental human rights violations and thus the high vulnerability of these women to violence, margin- alizing them and limiting their opportunities and the capacity to reduce the risks from their sexual activity, including HIV infection. A growing number of studies have demonstrated the convergence of structural factors and indirect risks 5,12,13 . A study on prevalence of gender violence against streetwalking female sex workers in Vancouver, Canada, found that 57% had suffered violence, correlated directly with macro-structural factors: lack of housing, criminalization of sex work, and difficult access to drug addiction treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The structural components of this profile, rooted in gender and class inequalities, reflect fundamental human rights violations and thus the high vulnerability of these women to violence, margin- alizing them and limiting their opportunities and the capacity to reduce the risks from their sexual activity, including HIV infection. A growing number of studies have demonstrated the convergence of structural factors and indirect risks 5,12,13 . A study on prevalence of gender violence against streetwalking female sex workers in Vancouver, Canada, found that 57% had suffered violence, correlated directly with macro-structural factors: lack of housing, criminalization of sex work, and difficult access to drug addiction treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[5,9,1416] Therefore, it is no wonder that FSWs are 13.5 times more likely to be living with HIV than other women, and are designated as a key population in relation to the HIV epidemic. [1,5,1720] Yet, the industry of sex work continues to thrive despite the high prevalence of HIV among FSWs, with the continued risk of transmission to their clients who include other vulnerable groups, such as LDTDs. [2,12]…”
Section: Introductionmentioning
confidence: 99%
“…Violence or the threat of violence by clients has been shown to reduce sex worker harm reduction practices such as safely negotiating male condom use, thereby increasing risk for HIV infection [11,[35][36][37][38][39]. Additionally, client-perpetrated violence has been highly associated with inability to access substance use treatment [7].…”
Section: Resultsmentioning
confidence: 99%